Instant Turkish Rice / Muhammad Fahmi Mohd Fauzi and Mohamad Isyraf Fauzi - Mohd Fauzi, Muhammad Fahmi; Fauzi, Mohamad Isyraf (2022)
Our group decided to produce a food product called "Instant Nasi Turki" which allows people to easily obtain turkey rice food quickly and immediately. We produce this Instant Turkish Rice in the form of MRE Heating Pack. Nasi Turki Instant contains delicious and high quality of rice with juicy meat, curry and some vegetable make this exclusive dish complete. This product is ready meal that can eat with simple preparations. For this new Instant Turkish Rice Product, we come with Chicken as the main dishes. We plan to add more dishes from time to time. Consumers can also carry this Instant Turkish Rice set anywhere due to its compact and lightweight packaging to carry. The use of quality ingredients in the processing of these food products. The idea to create this Instant Turkish Rice was started when we found out that to obtain this turkey rice is very difficult because this turkey rice can only be done by expert cooks only. When customers want to enjoy this turkey rice in the restaurant, they need to make a reservation in advance to get Turkish Rice. Moreover, we know that the demand is very high, and the price is quite expensive for this Turkish Rice. Therefore, we decided to produce this Instant Turkish Rice as our food product to be served to consumers. This product is Simple and Practical. The simple preparations and can bring to everywhere and anywhere to eat it. This instant food product is a very durable product.